Błękitna Dywizja w ujęciu Xaviera Moreno Juliá - Solak, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The outbreak of the German-Soviet war in June 1941 aroused enthusiasm in wide circles of Spanish society, still trying to heal its wounds after the revolution and civil war of the 1930s. Almost immediately there were calls for creating voluntary military units and sending them to Russia to fight against the hateful Bolshevism. This initiative is examined by Professor Xavier Moreno Juliá in his study The Blue Division. Spanish Blood in Russia, 1941–1945, a Polish edition of which was published in 2009. It still remains the most extensive and most comprehensive publication among works dealing with Franco’s Spain involvement on the eastern front available in Poland. In the article the author analyses the accuracy of the theses and opinions presented in the work in question, especially in the context of Polish approaches to the problem so far.
Keywords: Franco, Francisco (1892-1975); falanga; dywizje; krucjata; front wschodni; Stalin, Józef